Analysis of the Role of Agents in Improving Insurance Policies at PT. Prudential Life Assurance Binjai - Lily Khairani; Tri Inda Fadhila Rahma (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Insurance agent is someone who is a marketer in insurance products and has met the criteria and has qualifications as a licensed insurance agent in the implementation of insurance sales duties in accordance with their duties as determined by the company. Prudential is an insurance company that is present to provide life insurance services, with this life insurance service it is hoped that the community can maintain a lifestyle that avoids various life risks. This study aims to determine the role of agents from Prudential Companies in improving insurance policies. The type of this research is descriptive qualitative research. Data collection techniques used are library research and field observations, using document studies and interviews. The focus of this study is to analyze the effect of the agent's role in improving Prudential's insurance policy. Based on the analysis that has been carried out, the results of the agent's role in improving insurance policies are quite important. Success in selling policies is very dependent on the performance of agents owned by an insurance company.